Role of Artificial Intelligence-Enabled Marketing Strategies on Purchase Decisions - Latha, R. S; Chandran, M (Indian Journal of Information Sources and Services, 2025)
Modern science's knowledge and technology contributed significantly to transforming all marketing strategies into the strongest digitalization phenomenon, which has triggered a scientific technological revolution across industries. The main objectives of the study are to enumerate and validate all the components of artificial intelligence-enabled marketing strategies and to ascertain the existing factors responsible for the purchase decision process of customers in the study area. The researcher adopted the convenience sampling method and collected 467 samples from the study area. It is concluded that there is a significant influence of customer needs, customer expectation, price consciousness, quality consciousness, and perceived prestige on the psychological effects of purchase decisions of customers. These factors motivate them to analyze the important requirements of the product, its utility, attributes, and extraordinary performance. Keywords: AI-Marketing, Digitalization, Purchase-Behavior, Psychological-Factors, Customer-Expectations